(untitled) (AYUSHDHARA, 2022)
In the vast literature of Ayurveda, orthopaedic condition is well elaborated in the name of Bhagna Chikitsa. As per the condition Acharya Sushruta described Many of the new techniques are well developed for the management of fracture like as it’s etiology, classification, and various modalities of the management. Bhagna in ancient period were commonly faced problem occurs in war and attack by animal etc. but in the present time these are commonly as a result of Road Traffic Accident (R.T.A.). Acharya Sushruta explained Bhagna depending upon nature of trauma, shape of fracture, displacement of fracture fragment and fracture with or without wound. If it occurs in the bone it is called as Kand Bhagna (bone fracture) and in the joint it is called as Sandhimoksha (dislocation). Acharya Sushruta defined the principle of fracture of fracture management centuries ago are as per condition suggestive conservative or surgical treatment. Conservative modalities includes Kushabandh, Alepa, Chakrayoga, Taila Droni etc are still relevant and used. It would be worthwhile to explore this unique feature for use in present times. The concept, theories and techniques which were practical several thousand years ago hold true even in modern era. Purpose of this article, to re-evaluate the Bhagna.